Transition to working life and benefits of education as experienced by the graduates of an international master's programme in sport management - Pitkänen, Auli (2017)
University graduates in today’s working life need various skills in addition to the subject specific knowledge of the academic discipline. There is need, for instance, for the ability to use, create and produce knowledge, integration of theory into practice and oral and written presentation skills. All of this challenges the contemporary higher education institutions to integrate these elements into the curriculum to meet the above-mentioned demands. The purpose of this study was to find out, how the graduates an international Master’s Programme in Sport Management have moved to working life and how the education meets its needs, as experienced by the graduates. The data was collected with an electronic questionnaire during July-October 2015. Altogether 38 responses were received and the response rate was 49.3 per cent. The respondents were asked about their current working situation and longer career and the skills and competencies they need in their jobs. Furthermore, it was inquired how well the respondents felt they had received the required skills through the educational programme and if they had any suggestions to develop the programme further to better meet the demands of the current working life. The results showed that the employment situation was very good among the respondents as almost 80 per cent informed of working full-time. The most important tasks in the jobs of the graduates were planning and development tasks, communication and expertise in a special area. All in all, the respondents were rather satisfied with their current working situation. The most satisfied they were with the possibilities to influence the job, challenges the job provided and the flexibility of the working conditions. The least satisfied they were with their salaries. The respondents evaluated the educational programme as rather important and beneficial for their current jobs. As the most important skills received from the programme they listed communication skills, organisational skills and leadership skills. According to the respondents the international and multicultural group of students together with the multidisciplinary approach are also assets of the programme. On the other hand, in several occasions the respondents requested for more business management content to be added into the curriculum, as they felt that the field of sport management is getting more business-oriented and professional, and thus, skills in this area are needed. Additionally, there were several requests to increase the cooperation between the programme and employers to help the students in creating networks and receiving information on the important skills needed in the working life. The results of the study can be used to develop the programme further for it to better meet the needs of the working life and to give the current and future students tools to utilise the programme contents to the fullest in relation to finding a suitable job after graduation.